Early vs Late Anticoagulation After Ischemic Stroke in Patients With Atrial Fibrillation and Covert Brain Infarcts. - Kneihsl, Markus; Hakim, Arsany; Goeldlin, Martina B.; Meinel, Thomas R.; Branca, Mattia; Rohner, Roman; Fenzl, Sabine; Abend, Stefanie; Shim, Gek C.; Gumbinger, Christoph; Zhang, Liqun; Kristoffersen, Espen Saxhaug; et al. (Neurology, 2025)
BACKGROUND AND OBJECTIVES: Covert brain infarcts (CBIs) in patients with first-ever ischemic stroke (IS) and atrial fibrillation (AF) are associated with an increased risk of stroke recurrence. We aimed to assess whether CBIs modify the treatment effect of early vs late initiation of direct oral anticoagulants (DOACs) in patients with IS and AF. METHODS: We conducted a post hoc analysis of the international, multicenter, randomized-controlled ELAN trial, which compared early (<48 hours after ischemic stroke for minor and moderate stroke, 6-7 days for major stroke) vs late (>48 hours for minor, 3-4 days for moderate, 12-14 days for major stroke) initiation of DOACs in patients with IS and AF. The primary outcome was a composite of recurrent IS, symptomatic intracranial hemorrhage (sICH), major extracranial bleeding, systemic embolism, or vascular death within 30 days after stroke; secondary outcomes were the individual components. We estimated outcomes based on the presence of CBIs (any CBI vs no CBI) on prerandomization imaging (core-lab rating) using adjusted risk differences (aRDs) between treatment arms. Point estimates and 95% CIs are presented without reporting p values. RESULTS: Of the 1,694 participants with first-ever IS included (median age: 77 years, 45.9% female), 678 (40.0%) had CBI. The imaging core-lab interrater reliability for the presence of CBI was 0.87 (0.81-0.94). The primary outcome occurred in 8 (2.3%; recurrent IS: 3/342) of 342 participants with CBI assigned to the early treatment arm vs 20 (6.0%; recurrent IS: 12/336) of 336 assigned to the late treatment arm (aRD: -3.6%, 95% CI -6.6 to -0.6) (p for interaction: 0.063). With early DOAC treatment, IS recurrence risk was lower in participants with CBI (aRD: -2.7%, 95% CI -5.0 to -0.4), but not in participants without CBI (aRD: -0.4, 95% CI -2.1 to 1.2). No sICH was observed in the early treatment group. DISCUSSION: The presence of CBI may indicate a subgroup of patients with first-ever IS and AF who particularly benefits from early DOAC initiation to prevent ischemic event recurrence, without increasing harm. Our findings should be considered in clinical decision making regarding timely DOAC treatment in patients with stroke and AF. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that in patients with covert brain infarcts, atrial fibrillation, and first-ever ischemic stroke, early (vs late) initiation of DOACs is associated with lower risk of recurrent stroke with no increase in harm. TRIAL REGISTRATION INFORMATION: URL: clinicaltrials.gov/study/NCT03148457; Unique identifier: NCT03148457; submitted: April 7, 2017; first patient enrolled: November 6, 2017.
EVALuna2:607368